The Influence of Open Selection and Official Competence in Filling Primary High Leadership Positions on the Organizational Performance of Regional Apparatus in East Belitung Regency - Mudiarsono Mudiarsono; Nana Sulaksana; Budi Muljana (Budapest International Research and Critics University, 2021)
The Merit System and the available options are applied in many Agencies, Institutions and Local Governments to get the best Human Resources. The objectives of this research was to ascertain the impact of open selection and competence on the performance of regional apparatus organizations in the East Belitung Regency. This study employs an explanatory approach with a quantitative approach, analyzing data using descriptive statistics and multiple linear regression. The findings indicated that open selection had a major impact on organizational performance in part. Meanwhile, integrity has a major effect on organizational success on a partial basis. Simultaneous effects of open selection and competence on organizational efficiency are also important.